Frontiers in Algorithmics Second International Workshop, FAW 2008, Changsha, China, June 19-21, 2008, Proceedings - Preparata, Franco P.; Wu, Xiaodong; Yin, Jianping (Theoretical Computer Science and General Issues,, 2008)
This book constitutes the refereed proceedings of the Second International Frontiers of Algorithmics Workshop, FAW 2008, held in Changsha, China, in June 2008. The 33 revised full papers presented together with the abstracts of 3 invited talks were carefully reviewed and selected from 80 submissions. The papers were selected for 9 special focus tracks in the areas of biomedical informatics, discrete structures, geometric information processing and communication, games and incentive analysis, graph algorithms, internet algorithms and protocols, parameterized algorithms, design and analysis of heuristics, approximate and online algorithms, and machine learning.